The Contribution of Mental Capacity to Personality Formulation. An Overview - Antonopoulou, Hera (Technium Education and Humanities, 2024)
Mental capacity, encompassing cognitive abilities, emotional intelligence, and reasoning skills, plays a pivotal role in shaping one’s personality. This study delves into the intricate relationship between an individual’s mental faculties and their personality construct. Drawing from empirical research and theoretical frameworks, we posit that mental capacity influences not only the expression of personality traits but also their adaptability and resilience in various contexts. Higher cognitive abilities may correlate with increased self-awareness, complex problem-solving, and nuanced social interactions, all of which inform personality dynamics. Furthermore, variations in emotional intelligence can determine how individuals perceive, process, and respond to emotional stimuli, directly impacting interpersonal relationships and self-concept. By understanding the profound influence of mental capacity on personality formulation, this research sheds light on the multifaceted nature of human identity, emphasizing the symbiotic interplay between cognition and character.